A Novel Instrumental Method for the Determination of Cobalt (II) ion using NAG-ADF-300-2 Analyser, via the Formation of a Precipitating Reaction Product Through On-Line Long Distance (300 mm) and Short Path Length (2 mm) Chasing of Sample Segment - Nagam Shakir Turkie Al-Awadi (Journal of Global Pharma Technology, 2016)
A new instrument is presented for determination of Co (II) ion using precipitation reaction NAG-ADF-300 – 2 analyser is used for attenuation of incident light (white snow light emitting diode) at two stages, first one is 110 mm while the second one is 60 mm with a separation distance of 100 mm reaction of Co (II) ion with rubeanic acid in alkaline medium forms a black precipitate. The attenuation of this precipitate to the incident light is measured in a very repeatable, reproducible manner of RSD% less than 1% at variable concentrations. Line or calibration graph extend from 0.02 – 0.1 mmol / L Cobalt (II) ion. 30 sample / hr. can be handled. This instrument is easy to use and have extended ranged of working parameters. 50-500 µL samples can be manipulated using 2- line system. Limit of detection (L.O.D) is 0.5µmol L-1 at 50 µL for cell A and 7 µmol L-1 at 200 µL sample volume for cell B. The method was applied successfully for the determination of Co (II) ion in two different alloys.Key word: Turbidometry, Flow injection analysis, Cobalt (ll) Ion. and snow white light emitting diode.